The Reintegration of Former Jihadist Detainees in Solo Region: Changing A Way of Life in A New Life - Gitaningrum, Indah; Ahnaf, Mohammad Iqbal (Analisa: Journal of Social Science and Religion, 2021)
In the process of deradicalization, the reintegration of former jihadist detainee places as the most dilemmatic agenda to conduct. It raises a problematic situation between the issue of security and restoring the former jihadist detainees’s human rights. But, the struggle in the reintegration process not only occurs to the state and host community but also to the former jihadist detainees itself.  This paper focuses on the story of former jihadist detainees in Solo region who have  different experiences in their reintegration process and their strategies to encounter the problem as an effort to erase the radical thinking and start a new life. Solo Region was chosen because it receives a 'stigmatization' as a cultivation region for religious radicalism because of its record on radical Muslim's web and figure such as Abubakar Baasyir (the founder of Islamic radical group namely Jemaah Islamiyah). It also becomes a growing place for Islamic radicalism groups such as Jamaah Ansharut Daulah (JAD) and Jamaah Islamiyah which contributed toward Makassar’s Cathedral bombing, Bali bombing I and II and Laskar Jihad and Majelis Mujahidin Indonesia which tried to enforce Islamic value in Indonesia. The data of this research was gained by conducting an in-depth interview with four former jihadist detainees in Solo region who are willing to be interviewed under the pseudonym. Also, exposure some references as the secondary data. This article found that a sustainable, gradual, and comprehensive reintegration process in social, ideological, political, and economic aspects could support the effort of former jihadist detainees in the Solo region to establish a new life.